2004
DOI: 10.1136/jcp.2004.018952
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy and malignancy: an unsolved equation

Abstract: Aneuploidy is frequently noted in malignant tumours. There is much controversy about its cause and effect in relation to malignant tumours. Failure of the spindle checkpoint caused by mutation of the responsible genes may be one of the important factors for the development of aneuploidy. Telomere dysfunction may also be a possible source of failure of cytokinesis resulting in aneuploidy. Evidence such as tumour specific aneuploidy, presence of aneuploidy in various preneoplastic conditions, increased frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 63 publications
1
54
0
3
Order By: Relevance
“…The centrosome amplification leads to tumorigenesis through abnormal cell division and resulting chromosome instability. 4,7,36,44,45 Thus, it would be interesting to investigate whether elevated levels of USP1 correlates with increased centrosome abnormalities in human cancers. In summary, we have demonstrated for the first time that Usp1 plays a novel role in regulating centrosome duplication.…”
Section: Discussionmentioning
confidence: 99%
“…The centrosome amplification leads to tumorigenesis through abnormal cell division and resulting chromosome instability. 4,7,36,44,45 Thus, it would be interesting to investigate whether elevated levels of USP1 correlates with increased centrosome abnormalities in human cancers. In summary, we have demonstrated for the first time that Usp1 plays a novel role in regulating centrosome duplication.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal instability and aneuploidy, the gain and loss of chromosomes, is a characteristic of most malignant cells that is seen during the early stages of tumor development (1,2). It is thought that such alterations lead to the deregulation of the signalling network within the cells with the loss of tumor suppressor genes and the overexpression of oncogenes that drive tumorigenesis (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…It is a common molecular pathological characteristic in human carcinoma (7,15,16). A number of studies have suggested that using DNA probes for the detection of aneuploidy in cancer cells may be a superior technique to conventional pathological diagnosis (8)(9)(10)(11)(12)14).…”
Section: Discussionmentioning
confidence: 99%